Perdagangan Manusia Di Nusa Tenggara Timur (NTT) Tahun 2016-2017 - Elisabeth Palmini Bheni; Adi Joko Purwanto (Kajian Hubungan Internasional, 2021)
The Crime of human trafficking is a form of modern slavery and basically transnational in nature. East Nusa Tenggara is the province with the highest number of victims of trafficking in Indonesia, which continues to experience an increase in the number of victims each year. The purpose of this study was to determine the causes of human trafficking in East Nusa Tenggara 2016-2017. The study found that the increasing number of victims was caused by several factors. This study uses a qualitative descriptive method used through library research and interviews. From the results of the analysis using the concept of the Portuguese protocol there are several factors that are causes, namely poverty, education, culture, unemployment, and low law enforcement. To overcome human trafficking crimes in East Nusa Tenggara, intervention from many parties is needed to eradicate the factors that make it easy for people to become human trafficking.